2013
DOI: 10.1111/bph.12077
|View full text |Cite
|
Sign up to set email alerts
|

The antibiotic azithromycin is a motilin receptor agonist in human stomach: comparison with erythromycin

Abstract: BACKGROUND AND PURPOSEThe antibiotic azithromycin is a suggested alternative to erythromycin for treating patients with delayed gastric emptying. However, although hypothesized to activate motilin receptors, supportive evidence is unavailable. This was investigated using recombinant and naturally expressed motilin receptors in human stomach, comparing azithromycin with erythromycin. EXPERIMENTAL APPROACH[ 125 I]-motilin binding and calcium flux experiments were conducted using human recombinant motilin recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 33 publications
1
63
0
2
Order By: Relevance
“…19 Despite the controversy of the cellular mechanism of prokinetic & other effects of erythromycin on various parts of the gastrointestinal tract in different species, the prokinetic effect of erythromycin is confirmed beyond doubt in humans. [4][5][6][7][8][9][10][11][12][13] In conclusion, the present study shows that erythromycin base has different effects on different parts of the gastrointestinal tract in different species of animals in vitro. The cellular mechanism of effects of erythromycin on various parts of gastrointestinal tract is still not known with certainty.…”
Section: Fig 2a: Erythromycin (Em) 100 and 300 μM Reduced The Magnitudmentioning
confidence: 83%
See 2 more Smart Citations
“…19 Despite the controversy of the cellular mechanism of prokinetic & other effects of erythromycin on various parts of the gastrointestinal tract in different species, the prokinetic effect of erythromycin is confirmed beyond doubt in humans. [4][5][6][7][8][9][10][11][12][13] In conclusion, the present study shows that erythromycin base has different effects on different parts of the gastrointestinal tract in different species of animals in vitro. The cellular mechanism of effects of erythromycin on various parts of gastrointestinal tract is still not known with certainty.…”
Section: Fig 2a: Erythromycin (Em) 100 and 300 μM Reduced The Magnitudmentioning
confidence: 83%
“…15 It has been shown that erythromycin interacts directly with the motilin receptor and exerts agonistic action and also causes stimulation of the cholinergic system which may be responsible for its effects on gastrointestinal motility. 12,14 In animal experiments conducted both in vitro and in vivo, equivocal findings have been reported hence in the present study qualitative effect of erythromycin was studied on isolated rat colon, guinea pig ileum and rhythmically contracting rabbit jejunum.…”
Section: Comparison Of Effect Of Erythromycin (Em) 10 µM After 15 Minmentioning
confidence: 86%
See 1 more Smart Citation
“…The median (IQR) age for infants prescribed erythromycin and azithromycin was 49 days (23-70) and 68 days (50-80; P , .001), respectively. The median number of days after exposure to erythromycin in which the 17 infants underwent pyloromyotomy was 13 days (range, 2-40; IQR, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The median number of days between exposure to azithromycin in the 8 infants and subsequent pyloromyotomy was longer than the interval for the erythromycin group at 29.5 days (range, 9-45; IQR 20.5-38.5; P = .08).…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Similarly, azithromycin acts as a motilin receptor agonist and causes long-lasting facilitation of cholinergic activity in experiments by using circular muscle of human gastric antrum. 16 Azithromycin has also been shown to stimulate antral activity and induce migrating motor complexes in the duodenum in patients with gastrointestinal dysmotility. 17,18 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%